Recurrent atypical fibroxanthoma of the limbus. (15th March 2013) - Ullrich, Katja; Wells, Jane; Brennan, Catriona; Craig, Jamie
Abstract : We report an unusual presentation of recurrent atypical fibroxanthoma of the limbus. Clinical and histological appearances, as well as management are discussed and the current literature is reviewed.